Bank social fund distribution and cost of profit-sharing investment account: evidence from Indonesia - Prabowo Yudo Jayanto; Hasan Mukhibad; Nana Abdul Aziz (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to prove the impact of the distribution of social funds (qardhul hasan-QH and zakah funds) on the cost of a Profit-Sharing Investment Account (PSIA) immediately and for a long period in Islamic banks.Method - The research is based on panel data from 11 Islamic commercial banks (IB) in Indonesia from 2009 to 2021. Data were analyzed using the generalized least squares (GLS) random-effects method with robust standard error.Result - This research proves that the distribution of social funds (the distribution of QH and zakah funds) has a positive economic impact in the short period but the distribution of social funds has a negative economic impact in the long period.Implication - This study contributes to bank directors in considering the social activities of banks funded by QH funds by considering the effectiveness of social fund distribution, hence having positive economic consequences for bank performance.Originality - This research contributes to the development of previous literature in two ways. First, we use CSR performance proxies that are different from previous studies, namely the distribution of QH and zakah funds. The distribution of these funds is a proof of the bank's legitimacy to care about social, economic, and environmental issues. Second, we use the cost of PSIA as an economic consequence of CSR performance.